2004
DOI: 10.1117/12.510180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface roughness on large-volume CdZnTe nuclear radiation detectors and removal of surface damage by chemical etching

Abstract: This study investigates the effectiveness of chemical etchants to remove surface damage caused by mechanical polishing during the fabrication of Cd 0.9 Zn 0.1 Te (CZT) nuclear radiation detectors. We evaluate different planar CZT devices fabricated from the same CZT crystals. All detectors used electroless Au for the metal contacts. Different polishing particle sizes ranging from 22.1-µm SiC to 0.05-µm alumina were used, which caused different degrees of surface roughness. Current-voltage measurements and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Wright reported the decrease of the leakage current after NH F H O passivation [6]. However, the leakage current was reported to be increased after immersion in a NH F H O solution from the work by Prettyman and Wright [8], [9]. It was assumed that the NH F H O solution could affect the metal contact; however it was not clearly understood [9].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Wright reported the decrease of the leakage current after NH F H O passivation [6]. However, the leakage current was reported to be increased after immersion in a NH F H O solution from the work by Prettyman and Wright [8], [9]. It was assumed that the NH F H O solution could affect the metal contact; however it was not clearly understood [9].…”
Section: Discussionmentioning
confidence: 95%
“…Many researchers have shown that NH F H O solution could be one choice for the CZT surface passivation. In the previous work [6], [9], it was reported that the detector performance was enhanced after immersion of the detector into a NH F H O solution. Wright reported the decrease of the leakage current after NH F H O passivation [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reliable surface control is difficult to achieve with simple mechanical polishing; a more reliable method would be to use a chemical process (surface passivation). We have achieved the best performance results from fabricated detectors by applying a chemical treatment in which highly polished crystals were submersed for several minutes in a NH 4 F/H 2 O 2 solution [19].…”
Section: Virtual Frisch-grid Devicesmentioning
confidence: 99%